Preference for Comprehensive Dental Treatment under General Anesthesia among Parents with Previous Experience: A Cross-Sectional Study - Sara M. Bagher; Heba Jafar Sabbagh; Alaa Nadhreen; Najlaa M. Alamoudi; Abdullah Almushayt; Manal Al-Malik; Maha R. Al Shehri; Heba Mohamed Elkhodary (MDPI AG, 2023)
This study aims to assess whether parents of children who previously received comprehensive dental treatment under general anesthesia (GA) would prefer comprehensive dental treatment under GA over regular dental care if any of their other children required comprehensive dental treatment. In this cross-sectional study, parents of children who met the inclusion criteria were interviewed by a trained pediatric resident about parental-related factors as well as their satisfaction with their previous GA experience. Also, the factors related to the previously treated child were obtained from dental records. Statistical analysis was carried out, and the p value was set to 0.05. A total number of 306 parents were included. Although most parents, 293 (95.8%), showed satisfaction with the previous GA, 170 (58%) of the satisfied parents preferred regular care. Parents of children who were previously treated under GA for medical-related reasons (p = 0.018), fathers working in a governmental sector (p = 0.021), and families with low-average monthly income (p = 0.017) significantly preferred regular care. In conclusion, most parents were satisfied with the previous GA experience. Family income, fathers' occupation, and medical-related factors can influence parental preference for comprehensive dental treatment under general anesthesia if any of their other children require comprehensive dental treatment.